SWOT Identification in Green Plant Export Market Development - Tafuli, Maria Magdalena; Purnomo, Hery (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To identify the strengths, weaknesses, opportunities, and threats (SWOT) in leveraging digital innovation for the development of green plant export markets in the digital era. Design/Methode/Approach : This study employs a qualitative descriptive approach, using in-depth interviews, direct observation, and document analysis to collect data on strategies, challenges, and the application of digital technology in the green plant export business. Research Finding : The study identifies primary strengths, including high product quality and digital innovation in marketing. Weaknesses such as limited production capacity and a lack of skilled labor were noted. Opportunities include the growing trend of ornamental plants and government support, while threats encompass international competition, strict export regulations, and climate change impacts. Theoretical contribution/Originality : This study contributes to the literature by providing a comprehensive SWOT analysis of digital innovation in the green plant export market, highlighting its potential for enhancing competitiveness and sustainability in global markets. Practitionel/Policy implication : The research recommends strategies for utilizing digital platforms to expand markets and increasing production capacity through government support. These insights can guide policymakers and practitioners in formulating effective strategies to optimize digital marketing and improve operational efficiency. Research limitation : This study focuses on qualitative data, and its findings are limited to the green plant export business context, requiring further research to validate these results across other sectors and regions.